Використання доповненої реальності у дитячій літературі - Луніна, К. (My University, 2020)
Augmented Reality is unusual, fantastic, modern and real-life technology that find its use in different sphere of design. From year to year, Augmented Reality develops and takes root in the modern system of human life
Keywords: доповнена реальність; дитяча література; 3D персонажі